PEMAHAMAN KESUKUAN DALAM KELUARGA MULTI-SUKU DI PONTIANAK - Indah Sri Wahyuni (Jurnal Pendidikan, Kebudayaan dan Keislaman, 2023)
In general, this research is motivated by the problem of the condition of knowledge in one of the multi-ethnic families in the komplek BLKI, Pontianak Tenggara, who still do not fully know about the ethnic they belong to. This was revealed after observing daily habits that do not describe the ethnic group used as the identity. The purpose of this study is to find out about: (1) The application of culture to multi-ethnic families in everyday life. (2) Knowledge of each member of a multi-ethnic family about the tribe they belong to. (3) General material about ethnic groups belonging to multi-ethnic families. (4) Factors influencing ethnic knowledge in multi-ethnic families. This research used qualitative methods in the form of observation and online interview. The data source for this research is one of the multi-ethnic families who live in the komplek BLKI, Pontianak Tenggara. As a result, the condition of ethnic knowledge in the family is not good. The discussion is that family members apply some of the tribal culture in everyday life, knowledge about the ethnicity that is owned is not much, the tribes that are owned are Malay and Bugis, the factors that influence knowledge in the multi-ethnic family are individual factors, heredity, and environmental factors. It can be concluded that the condition of ethnic knowledge in multi-ethnic families in the komplek BLKI, Pontianak Tenggara is still limited.